Does age influence the outcome of lower limb non-union treatment?: a matched pair analysis - Tanner, Michael Christopher; Vlachopoulos, Wasilios; Findeisen, Sebastian; Miska, Matthias; Ober, Julian; Hagelskamp, Saskia; Schmidmaier, Gerhard; Haubruck, Patrick (Journal of Clinical Medicine, 2019)
Background: Fractures in elderly patients are common and have severe implications on a socioeconomic level, as musculoskeletal integrity and competence is crucial for independence. Changes in both composition and biology of bones during aging potentially affect fracture healing adversely. The current study sought to determine the influence of age on the outcome of non-union therapy of atrophic and hypertrophic non-unions based on the “diamond concept”, as well as to evaluate the well-known risk factors impairing bone healing. Patients and Methods: All medical records, operative notes, lab data, and radiological imaging of patients that received surgical treatment of both atrophic and hypertrophic non-unions of the femur or tibia between 1 January 2010 and 31 December 2016 were thoroughly reviewed and analyzed. Patients who participated in our standardized follow-up for at least 12 months were included into a database. Patients older than 60 years were matched with patients younger than 60 based on five established criteria. The study was approved by the local ethics committee (S-262/2017). According to our inclusion criteria, a total of 76 patients older than 60 years were eligible for analysis. Via matching, two groups were formed: study group (SG; >60 years; n = 45) and control group (CG; <60 years; n = 45). Results: Twelve months subsequent to treatment, the consolidation rate was equivalent in both groups (SG: 71% vs. CG: 67%). The consolidation for all patients before matching was 73%. The clinical results for the complete collective were no pain or pain with high or medium strain for 62.5%, whereas 29.6% had pain with low strain or constant pain. 7.87% had no pain levels given. Logistic regression modeling showed no influence of age >60 years on radiological or clinical outcome, whereas a significant negative correlation was revealed between patients aged 40–49 years and radiological non-union consolidation (b = −1.145 and p = 0.048). In addition, diabetes had a negative influence on non-union therapy (b = −1.145 and p = 0.048). As expected, the clinical outcome correlated significantly with the radiological outcome (p < 0.001). Conclusion: Surgeons should optimize both modifiable risk factors such as diabetes mellitus, as well as surgical treatment in order to achieve the best possible outcome in elderly patients. Elderly patients benefit from osseous consolidation by enabling and maintaining musculoskeletal competence due to the close correlation between clinical and radiological outcome. Advanced age alone does not negatively influence the outcome of non-union therapy and should, therefore, not be considered a risk factor. In contrast, patients in their fifth decade suffering from lower limb non-unions should be considered as high-risk patients and treatment should be modified accordingly.
Gesehen am 19.02.2020